Kajian Semiotika dalam Sajak “Bilang” dan “Memilikimu” Karya Tere Liye - Ismi Arifah; Rahmi Suryati (Journal on Education, 2023)
The article entitled Semiotic Studies in the Poems "Bilang" and "Memilikimu" by Tere Liye is a semiotic study that discusses two poems by Tere Liye entitled, "Memilikimu" and "Bilang". The purpose of this research is to produce an interpretation that contains the theme of humanity with the problem of love in the two poems and to describe the meaning through signs that produce interpretations through the study of Semiotics. Analysis of the two titles of this poem uses a qualitative descriptive method. The approach used is Aart Van Zoest's semiotic approach. The technique that we use is the reading technique. The researcher reads the entire poem and then records the words, phrases and clauses to find signs that result in an interpretation that contains the theme of humanity with the value of love in the two poems. The results of the research are the poems entitled "Bilang" and "Memilikimu" which contain the theme of humanity which contains the meaning of love that does not reach and cannot have. In both poems, the dominance of incomplete sentence patterns was found, the dominance of phrases/words with meaningful denotations, and five figures of speech were found, including repetition, cynicism, allegory, hyperbole and parallelism. Meanwhile, the isotopes used in the two poems are character isotope, perception isotope, movement isotope, nature isotope, human isotope and space isotope. I lyrics in both poems use singular personal pronouns and plural personal pronouns. In addition, these poems are advice from poets to readers regarding matters of love.